Italy and the trap of GVC downgrading: Labour dependence in the European geography of production - Lorenzo Cresti; Giovanni Dosi; Federico Riccio; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
How does Italy position inside the European structure of trade relationships? How labour bilateral flows have changed over time? Which type of employment activity has been outsourced? Which insourced? Focusing on a three-country perspective, what are the employment bilateral relationships between Italy-Germany-Poland (descending periphery-core-ascending periphery)? To address these questions we develop a novel set of bilateral labour dependence indicators inside I-O production networks. Overall, we provide evidence of the reconfiguration of Italy as falling into the trap of GVC downgrading, with an increasing number of trade relationships in employment requirements, particularly in the most strategic productions, as insourced from abroad. The offshoring strategy conducted so far has resulted in a weakening of its internal production capacity and employment absorption, even more harshly when compared to other European countries.
Keywords: F66; F15; J21; O14; O52; 330; Input-output; global value chains; international division of labour; core-periphery